PENINGKATAN PHBS MELALUI PENYULUHAN DAN PEMERIKSAAN KESEHATAN UNTUK DETEKSI DINI PENYAKIT DEGENERATIF - Ilmannafia Azhar (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2026)
Degenerative diseases such as hypertension, diabetes mellitus, and hypercholesterolemia are non-communicable diseases (NCDs) with a continuously rising prevalence, including in island and rural areas with limited access to health services, such as Bante Hamlet, Wakatobi Regency. This activity aimed to improve community knowledge and practice of Clean and Healthy Living Behavior (PHBS) and to conduct early detection of degenerative diseases through free health education and examinations. The method consisted of interactive health education on PHBS and degenerative diseases, health examinations (blood pressure, random blood glucose, total cholesterol, and uric acid), and pre-test/post-test evaluation among 52 participants. The mean PHBS knowledge score increased from 56.9% (pre-test) to 85.3% (post-test). The examination found that 34.6% of participants had hypertension, 21.3% had elevated blood glucose, 28.8% had high cholesterol, and 25.0% had high uric acid, most previously unrecognized. The activity proved effective in improving PHBS knowledge and served as a means of early detection of degenerative disease, and should be conducted periodically with the local Puskesmas.